2020
DOI: 10.1109/lwc.2020.2982157
|View full text |Cite
|
Sign up to set email alerts
|

Q-Ary Multi-Mode OFDM With Index Modulation

Abstract: In this paper, we propose a novel orthogonal frequency division multiplexing with index modulation (OFDM-IM) scheme, which we call Q-ary multi-mode OFDM-IM (Q-MM-OFDM-IM). In the proposed scheme, Q disjoint M -ary constellations are used repeatedly on each subcarrier, and a maximum-distance separable code is applied to the indices of these constellations to achieve the highest number of index symbols. A low-complexity subcarrier-wise detection is shown possible for the proposed scheme. Spectral efficiency (SE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 13 publications
(45 reference statements)
0
11
0
Order By: Relevance
“…However, as will be shown in Fig. 2, a receiver performing only (10) and (11) in the presence of channel encoding fails to provide near-optimal error performance when N < 4. To solve this problem, instead of employing the MDS coding mechanism among symbol vectors, equivalent (N, N − 1) single parity check (SPC) code can be employed among information bits and the resulting bit sequence can be mapped to the symbol vectors.…”
Section: Log-likelihood Ratio Calculationmentioning
confidence: 89%
See 4 more Smart Citations
“…However, as will be shown in Fig. 2, a receiver performing only (10) and (11) in the presence of channel encoding fails to provide near-optimal error performance when N < 4. To solve this problem, instead of employing the MDS coding mechanism among symbol vectors, equivalent (N, N − 1) single parity check (SPC) code can be employed among information bits and the resulting bit sequence can be mapped to the symbol vectors.…”
Section: Log-likelihood Ratio Calculationmentioning
confidence: 89%
“…Performing the optimum ML detector in (4) requires excessive complexity when the size of the codebook, M , is high. To overcome this problem, we proposed low complexity ML (LC-ML) detectors in [10], [11] for the MDS modulation techniques and showed that these detectors perform close to the optimum ML detector while reducing the complexity significantly.…”
Section: B Receivermentioning
confidence: 99%
See 3 more Smart Citations